MicroRNA-520a Suppresses Pathogenesis and Progression of Non-Small-Cell Lung Cancer through Targeting the RRM2/Wnt Axis - Yi Xie; Congyu Xue; Shuai Guo; Lei Yang (Analytical Cellular Pathology)
MicroRNAs (miRNAs) regulate multiple cellular behaviors, and their aberrant expression is frequently associated with disease progression. This research focused on the effects of miR-520a on the development of non-small-cell lung cancer (NSCLC) and the molecules involved. Tumor and normal tissues from 24 patients with NSCLC were collected. Differentially expressed miRNAs between tumor tissues and normal tissues were screened using microarrays, and miR-520a was screened to be significantly poorly expressed in tumor samples. Artificial upregulation of miR-520a reduced proliferation, migration and invasion, and resistance to death of NSCLC A549 and H460 cells according to the MTT, EdU labeling, transwell, and flow cytometry assays, respectively. miR-520a upregulation suppressed growth and metastasis of xenograft tumors in vivo. The integrated bioinformatic analysis and dual luciferase assays suggested that miR-520a targeted ribonucleotide reductase subunit 2 (RRM2) mRNA and inactivated the Wnt/β-catenin signaling pathway in NSCLC cells. Upregulation of RRM2 enhanced the malignant behaviors of NSCLCs, but the oncogenic effects of RRM2 were blocked upon miR-520a overexpression. To conclude, this study evidenced that miR-520a inhibits NSCLC progression through suppressing RRM2 and the Wnt signaling pathway. This paper may offer novel insights into NSCLC treatment.